Supplier Selection Analysis of Rubber Raw Material Using TOPSIS Method - Dira Ernawati; Yekti Condro Winursito; Lutvia Agustin (Nusantara Science and Technology Proceedings)
Customer satisfaction is the main orientation of a company. To fulfill consumer desires, the company should pay attention to procuring raw materials and choosing the right supplier. Manufacturing companies have to think about how their products have added value compared to other companies. Company XYZ needs to determine the right strategy for purchasing rubber raw materials to increase the efficiency and effectiveness of the company. The method for analyzing the selection of suppliers of rubber raw materials is the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method with the weighting of the criteria obtained from the AHP calculation value. The TOPSIS method is used to sort alternative suppliers based on the closest distance from the alternative value to the positive ideal solution and the farthest distance from the perfect negative solution. The data processing results are compared to other suppliers with a value of 0.31088 and the distance of the farthest negative ideal solution from the others with a value of 0.22064. Rank 1: company C, Rank 2: company A, Rank 3: company E, Rank 4: company B, Rank 5: company D.